(untitled) (Journal of Guidance and Counselling Studies, 2016)
Youth restiveness in Nigeria has been a prominent issue in recent times. There has been an increase in the occurrence of acts of violence and lawlessness, hostage-taking of prominent citizens, oil bunkering, arms insurgence and cultism, etc. Nevertheless, youth restiveness is not a recent phenomenon. Youth restiveness can results from economically, politically, or religiously issues that manifest its self in all over the country, Nigeria.